Sikap Optimis di Masa Pandemi Covid-19 - Rosada , Amrina; Partono , Partono (Al-Insyiroh: Jurnal Studi Keislaman, 2020)
The purpose of this research is to find out how people respond to the Corona Virus pandemic (Covid-19) calmly and not rashly. The focus of this research problem is on how the community's role in implementing an optimistic attitude during the Covid-19 pandemic. This type of research is a qualitative research with a descriptive qualitative approach. The results of this study indicate that optimistic behavior displayed by the community is very important, so it must be improved. It is intended that Indonesian people are equally positive to face Covid-19. An optimistic attitude will increase body immunity so that the possibility of corona virus will be low. An optimistic attitude will maintain and enhance immunity. However, if stressed, it will also affect immunity. So that the community is asked to maintain a positive mindset one of which is optimistic and caring or unselfish, as well as following the government's recommendations such as social distancing, avoiding crowds, working from home, worshiping at home and appeals from other governments.